Formulation of Legal and Regulatory Models of Carbon Units as Collateral Objects in Indonesia - Diana Tantri Cahyaningsih; Dona Budi Kharisma; Alisha Vinia Alethea Majid (Faculty of Law, Universitas Pekalongan, 2025)
The rise in GHG emissions has driven countries, including Indonesia, to commit to Net Zero Emissions through the 2015 Paris Agreement. One of Indonesia’s efforts is limiting carbon emissions via carbon trading. The traded object, carbon units, are categorized as securities with economic value, presenting an opportunity to use them as collateral. However, theres is no clear regulation governing this. This normative legal research uses statute and conceptual approaches, with primary and secondary legalmaterials on collateral law. The study aims to propose regulatory recommendations to enable the use of carbon units as collateral in Indonesia. The findings suggest that fiduciary is the most suitable binding meyhod, as it does not require physical delivery and allows execution through private sale under Article 31 of Indonesia Fiduciary Law. The lack of a valuation institution can be addressed by optimizing collaboration between public appraisers, like KJPP and GHG Validation and Verification instituions (LV/V GRK).